2007
DOI: 10.1080/10410230701283272
|View full text |Cite
|
Sign up to set email alerts
|

After 9/11: Goal Disruption, Emotional Support, and Psychological Health in a Lower Exposure Sample

Abstract: The terrorist attacks of 9/11 were traumatic even for Americans who were not directly victimized or in the geographic vicinity. This study examined whether emotional support received through interaction with others buffered the association between terrorism-related stress and psychological health (depression, anxiety, and physical symptoms) for individuals with lower exposure to the attacks. Five hundred eleven college students from an eastern university completed measures of goal disruption (stress) from terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In relation to well-being, giving up on a cherished goal can be appraised as threatening, and thus stressful to the individual, which can result in negative feelings such as dissatisfaction, sadness, and distress (Carver & Connor-Smith, 2010). This proposition is supported by the general goal-disruption literature (MacGeorge, Samter, Feng, Gillihan, & Graves, 2007; Roseman & Smith, 2001), and consistent with reports in the career area. Carr (1997), for example, asked women who were in their mid-career to reflect on their past occupational goals, and found that those who were dissatisfied with their level of achievement, vis-à-vis their original expectations, were more likely to report symptoms of depression and to have less purpose in life.…”
Section: Career Compromise and Well-beingsupporting
confidence: 85%
“…In relation to well-being, giving up on a cherished goal can be appraised as threatening, and thus stressful to the individual, which can result in negative feelings such as dissatisfaction, sadness, and distress (Carver & Connor-Smith, 2010). This proposition is supported by the general goal-disruption literature (MacGeorge, Samter, Feng, Gillihan, & Graves, 2007; Roseman & Smith, 2001), and consistent with reports in the career area. Carr (1997), for example, asked women who were in their mid-career to reflect on their past occupational goals, and found that those who were dissatisfied with their level of achievement, vis-à-vis their original expectations, were more likely to report symptoms of depression and to have less purpose in life.…”
Section: Career Compromise and Well-beingsupporting
confidence: 85%
“…Stressful times call for support to be given to relationships or social groups, and emotionally supportive communication may provide an antidote to the stress provoked by terrorism (MacGeorge, Samter, Feng, Gillihan & Graves, ). As mentioned by Palenchar, Heath, and Orberton (, p. 65) in a study on terrorism and industrial chemical production, ‘A resilient community can live with rather than in fear’.…”
Section: Resultsmentioning
confidence: 99%
“…Many NGOs, influential celebrities and government institutions have provided aid to them to return safely to their villages and home towns. [2][3][4][5][6].…”
Section: Covid19 and Its Impact On Indiamentioning
confidence: 99%